A Critique of Modern Materialist Philosophy from the Perspective of Islam - Ahmad Hisyam Syamil; Amir Reza Kusuma (MAQOLAT: Journal of Islamic Studies, 2025)
This paper offers a critical analysis of modern materialist philosophy from an Islamic perspective. It argues that the spread of materialist thought—emerging prominently in the 19th century with ideologies like positivism, evolutionism, Marxism, pragmatism, and logical positivism—has fundamentally reshaped global intellectual discourse, often at the expense of metaphysical and spiritual values. The authors contend that these philosophies, while presenting themselves as “scientific” and “rational,” are unified in their denial of divine revelation, their reduction of reality to material phenomena, and their promotion of atheism. Drawing from the works of influential Western thinkers such as Karl Marx, Ernst Haeckel, and others, the paper highlights how materialism became the philosophical backbone of modern secular ideologies, particularly in education, politics, and economics. In contrast, the Islamic worldview maintains that reality encompasses both the seen and unseen, and that true knowledge must integrate reason, revelation, and empirical observation. The authors also reference contemporary Muslim scholars who have critically engaged with these ideologies, proposing methodological reforms in Islamic theology to better respond to the epistemological challenges posed by materialist philosophies. Ultimately, the paper asserts that modern materialism not only contradicts core Islamic tenets about God, man, and the universe but also leads to moral and existential crises by excluding transcendental values. Thus, a comprehensive Islamic critique is essential not only to defend the integrity of Islamic thought but also to contribute constructively to global philosophical debates